Análise da dinâmica da evolução do valor de empresas brasileiras de capital aberto nos setores de mineração e siderurgia no período: 2002-2012 - Silva, Antonia Ana Neri Galdino e (2014)
The study aims to evaluate the dynamics of evolution of corporate value; described by the variables Equity and Enterprise Value, the publicly traded companies in the mining and steel sector listed on the BOVESPA, between January 2002 and December 2012, which contributes with to the literature to use as a tool to analyze an autoregressive model with endogenous threshold value, and helps to capture changes on the default value of the companies placed on our current scenario and economic policy, to provide a more fair value of companies in the future since their use is of utmost importance to business decision-making and other purposes. Quantitative indicators for these two variables were calculated and the methodology allowed to investigate both the linearity and stationarity of their trajectories. The results showed, through the selected variables, three different situations among the selected companies: i) linear dynamics, non-stationarity for Equity and Enterprise Value, reaches Ferbasa and Equity the Vale; but the Enterprise Value of the Vale follows a stationary dynamics;ii) non-linear dynamics, which follows a pattern change in selected variables for Equity and Enterprise Value additionally non-stationarity in the two regimes, for Equity and Enterprise Value reaches Gerdau and Usiminas; and iii) non-linear dynamic for Equity and linear for the Enterprise Value for the National Steel Company, which additionally presents for Equity partial and globally stationary unit root, dynamic and Enterprise Value presents non-stationarity.